Application of Manual Therapy for Dysphagia in Head and Neck Cancer Patients: A Preliminary National Survey of Treatment Trends and Adverse Events - Gintas P Krisciunas MPH, MA; Aneri Vakharia BS; Cathy Lazarus PhD; Stephanie Gomez Taborda BS; Rosemary Martino PhD; Katherine Hutcheson PhD; Timothy McCulloch MD; Susan E Langmore PhD (SAGE Publishing, 2019)
Background Radiation-associated dysphagia is a common and debilitating consequence of treatment for head and neck cancer (HNC). Since commonly employed dysphagia therapy programs for HNC patients still lack authoritative efficacy, some speech-language pathologists (SLPs) have started employing manual therapy (MT) techniques in an attempt to prevent or rehabilitate dysphagia in this patient population. However, exceptionally little is known about the use of MT in this patient population. Objectives The purpose of this study was to describe practice patterns as well as the rate, type, and severity of adverse events associated with SLP provision of MT to HNC patients. Methods An Internet-based questionnaire geared toward SLPs who practice MT was developed and sent to SLPs practicing in the United States, 3 times, through 3 national listservs (American Speech Language Hearing Association [ASHA] Special Interest Division 13, ASHA Special Interest Division 3, and University of Iowa Voiceserv), over the course of 4 weeks. Results Of the 255 respondents, 116 (45.5%) performed MT on HNC patients. Of these 116 SLPs, 27.6% provided proactive MT during radiation, 62.1% provided 1 to 2 sessions per week, and 94.8% prescribed a MT home program. The rate, type, and severity of reported adverse events were similar between HNC and non-HNC patients. Conclusion This preliminary survey demonstrated that SLPs provide MT to HNC patients during and after cancer treatment, and that reported adverse events paralleled those experienced by noncancer patients. However, these results should be taken with caution, and a well-designed prospective study is needed to formally establish the safety and the preliminary efficacy of this novel clinical intervention.